Identifikasi dan Pengendalian Risiko Menggunakan Metode HIRARC Pada Pekerjaan Pengolahan Bahan Baku di PT. X - M. Nur, Agung Pratama Wijaya; Iriani, Iriani (Fakultas Teknik Universitas Tulang Bawang, 2025)
The cement producing industry has a high level of occupational accident risk due to the complexity of the production process and potential hazards at every stage of the work. PT X, faces the challenge of improving occupational safety risk management, especially at the raw material processing workstation. By utilizing the HIRARC (Hazard Identification, Risk Assessment, and Risk Control) method, this study aims to provide a systematic risk management solution to minimize work accidents that can impact worker safety and the company's operational efficiency and propose effective risk control measures at raw material processing work. The results of the study are based on a risk assessment in terms of raw material processing there are 13 potential hazards from 6 stages of the raw material processing work process. Each risk level at the raw material processing workstation includes an extreme level of 26%, a high level of 38%, a medium level of 27% and a low level of 9%. Hierarchy of Control method: elimination, substitution, engineering, administration and PPE are used for risk control. Keywords: HIRARC, Occupational Safety, Risk Control